Sosialisasi Satu Pohon Seribu Harapan: Gerakan Selamatkan Bumi, Dimulai dari Kita di SDN Mumbulsari 04 Jember - Kharisma Dwi Aprilia; Inge Wiliandani Setya Putri; Arik Aguk Wardoyo; Shinta Permata Dewi; Dea Puspitasari; Kirani Meilinda Saputri; Diah Indrajati Fauziyah Utami; Ninin Febi Yulianti (Assoeltan: Indonesian Journal of Community Research and Engagement, 2024)
Climate change is one of the biggest challenges for humans around the world today, especially Indonesia. Quoted from various world institutions including the World Meteorological Organization (WMO), the Intergovernmental Panel on Climate Change (IPCC), and the United Nations Framework Convention on Climate Change (UNFCCC), it is stated that climate change will continue to occur in the coming decades if no mitigation action is taken. This community service activity aims to increase awareness of students and school residents regarding the importance of reforestation as an effort to mitigate the climate crisis by planting trees on empty land around the school. The program uses the Participatory Action Research (PAR) method through socialization of the benefits of trees for the ecosystem, tree care steps, and active participation of school residents, especially students, in environmental conservation. The results of the community service activities show an increase in student understanding regarding the role of trees in absorbing carbon dioxide, producing oxygen, and maintaining ecosystem balance. Through this program, students and teachers are inspired to optimally utilize empty land as green space and become one of the solutions in mitigating the impacts of climate change that are increasingly being felt. Despite facing various challenges, such as the effects of weather to limited human resources. However, this movement has succeeded in creating a greener, more comfortable, and healthier learning environment. In order for these benefits to be felt more by all Indonesian people from various elements, we suggest the involvement of policy makers to integrate environmental education into the curriculum, collaboration with various sectors to support the provision of facilities and resources, such as tree seedlings, maintenance tools, and sustainable funding. In addition, a structured monitoring program is needed to ensure the sustainability of the movement.